Análise da pesquisa científica sobre Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) no Brasil a partir de indicadores bibliométricos - Silva, Rhaissa Michievicy Simões de Melo Cardoso da (Universidade Federal de São Carlos, 2015)
Brazilian agriculture is currently experiencing significant losses due to a recently introduced pest, the Helicoverpa armigera caterpillar. Belonging to the Heliothinae subfamily, it is an extremely polyphagous insect that has intensely attacked various crops of economic importance, including soybeans, cotton, corn, beans, and tomatoes. Scientometrics is the quantitative study of scientific production, allowing the evaluation of trends and contributions to research activities carried out by researchers, institutions, or countries in different areas of knowledge. Therefore, the objective of this study was to provide an overview of scientific research on H. armigera in Brazil based on bibliometric indicators. To achieve this, a survey of indexed scientific publications present in the SCOPUS® and Google Scholar® databases was carried out. Between 2005 and 2015, approximately 1,860 documents related to H. armigera were published worldwide. As the pest recently emerged in Brazil, only 22 publications were authored by Brazilian authors in the same period. Therefore, it is observed that the incidence of the pest in Brazil was the main motivation for starting research on the caterpillar in the country, whose management and control are urgently needed.
Analysis of scientific research on Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) in Brazil based on bibliometric indicators
Keywords: Bibliometria; Produção científica; Praga exótica; Lagarta; Plantas cultivadas; Bibliometrics; Scientific production; Exotic pest; Caterpillar; Cultivated plants; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE